Teacher Experiences of Using Digital Technology to Support Reading Development in Grade 1 Learning Contexts - Dadabhai, Qudsiyyah (University of the Witwatersrand, Johannesburg, 2024)
The 2021 Progress in International Reading Literacy Study (PIRLS) revealed a literacy crisis in South Africa, with 81% of Grade 4 learners unable to read for meaning in any of the nine official languages. Research suggests that the perceptive use of digital technology can enhance reading proficiency. This qualitative study examined teachers' experiences of using digital technology to support reading development in Grade 1 classrooms in South Africa. Using the TPACK framework, semi-structured interviews and classroom observations were conducted with four Grade 1 teachers in Johannesburg. Findings revealed that teachers' technological knowledge varied significantly, influencing their integration of digital technology into reading lessons. Several factors inhibited teachers' use of digital technology, including varying levels of technical expertise, inconsistent stakeholder support, classroom management challenges, difficulties in balancing books and screens, and the emotional labour associated with using technology to support reading development. While digital technology shows potential for improving reading comprehension and fluency, its effective implementation is hindered by contextual limitations and the need for specialised teacher training. The lack of support from schools, parents, peers, and other relevant stakeholders prompted teachers to exercise agency in integrating digital technology into reading instruction, albeit with difficulties. The study highlights the importance of formal training to effectively incorporate digital technology into Grade 1 reading spaces. Additionally, it emphasises the need for comprehensive support from all stakeholders to facilitate the integration of digital technology into classroom lessons, ultimately aiming to improve reading proficiency in Grade 1.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; digital technology; integration; TPACK; fourth industrial revolution; professional training; SDG-4: Quality education